Fundamentals of tour guide in Muslim Friendly Tourism - Jamaludin, Mohammad Aizat; Rosli, Nur Liana Izzaty; Saffinee, Siti Syahirah (HH Publisher, 2023)
This study aims to explore the concept and characteristics of being a tour guide in Muslim-friendly tourism. The study identifies tour guides need to possess effectively and cater the needs of Muslim travellers and provide them with a positive and inclusive travel experience. The research utilizes a qualitative approach, employing data collection based on secondary resources such as books, journals, and articles. The findings of this study contribute to a better understanding of tour guides in Muslim-friendly tourism and provide practical recommendations for tour guides to enhance their services for Muslim travellers.